The introduction of document study to the Western Australian ancient history course and its implications for pedagogy - Moon, Annette Julie (Curtin University, 2013)
This study investigated the impact of the introduction of Document Study to the Western Australian Senior Secondary Ancient History Course in 2009–2010. A survey of the literature suggested a new set of skills and a revised pedagogical approach is required to teach the historical skills and concepts necessary for document study. Thus, a primary focus of the study was the implications for teaching practices, which flow directly from this change in the curriculum and assessment regime. The literature also pointed to a number of factors that may determine a teacher’s preparedness to adopt and successfully teach the requisite skills for document study. These factors, along with the teachers’ responses to and perceptions of the curriculum and assessment change, have been explored. The survey instruments were constructed specifically for this study using a theoretical framework derived from the literature and confirmed by the results of a pilot survey of two curriculum experts. A sample of thirteen practising Ancient History teachers was surveyed using a questionnaire to elicit quantitative and qualitative data. The data from the survey were analysed using descriptive statistical methods and content analysis.The results of the survey revealed that the curriculum change had indeed impacted significantly on the teaching of Ancient History, with all of the participants reporting the necessity to change their teaching practices through the introduction of new historical skills and concepts and to employ new strategies for teaching their students to conduct document studies. Three clusters emerged from the data based on the content analysis of the responses: negative perceptions of the change, positive perceptions of the change, and neutral responses. Analysis of the quantitative and qualitative data supported the findings of the literature that factors such as personal view of history, educational background, and professional development experiences could have an impact on how readily a teacher adopted the new skills, concepts and methodology required to teach document study. Interrelationships were revealed between such factors as personal view of history and acceptance of the new historical skills and concepts. The findings provide strategies for better-targeted professional development and pre-service training for History teachers. The adoption of the Australian Curriculum History course in Western Australia may mean that the findings have broader implications. Teachers in Primary Schools and Lower Secondary Schools will need to become familiar with document study techniques in order to teach the new compulsory History curriculum. Currently few Primary School teachers have training in History methodology and many Lower Secondary Society and Environment teachers are trained in disciplines other than History (Geography, Economics, Politics, and Law among others).